죽엽(솜대)의 항산화 성분 및 구강세균에 대한 항균 효과 - 박경란(Kyung Lan Park); 강성태(Sung Tae Kang); 김민주(Min Ju Kim); 오희경(Hee Kyung Oh) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2016)
The objective of this study was to investigate the antioxidative components and anti-oralmicrobial effect of bamboo (Phyllostachys nigra var. henonis Stapf) leaves. The moisture, crude protein, crude fat, crude ash, and carbohydrate contents were 6.30%, 5.10%, 1.73%, 10.61%, and 76.26%, respectively. Vitamin C content was higher than Vitamin A and E contents. Among organic acids, citric acid content was the most abundant organic acid, followed by succinic acid, acetic acid, malic acid, and formic acid. Total polyphenol and flavonoid contents were 21.66 mg/g and 42.78 mg/g, respectively. Minimum inhibitory concentrations (MICs) of extracts of bamboo leaves for Streptococcus mutans and Streptococcus sobrinus were determined to be 0.04% and 0.16%, respectively. MICs of extracts of bamboo leaves for Porphyromonas gingivalis and Prevotella intermedia were determined to be 0.02%. Extract of bamboo leaves had strong antimicrobial activity against S. mutans, S. sobrinus, P. gingivalis, and P. intermedia at a concentration of 0.32%. At this concentration, extract of bamboo leaves inhibited growth of these pathogenic bacteria up to 60 h. The results of the present study demonstrate the antimicrobial effects of bamboo leaves ethanol extract against oral pathogenic bacteria, suggesting that bamboo leaves could be an effective natural agent for oral hygiene. 본 연구에서는 죽엽(솜대)의 항산화 성분을 조사하고 구강질환 세균에 대한 죽엽 추출물의 항균 활성을 검토하였다. 죽엽의 일반성분은 탄수화물 76.26%, 조회분 10.61%, 조단백질 5.10%, 수분 6.30%, 조지방 1.73%였고, 비타민 A 및 E의 함량에 비하여 비타민 C 함량은 월등히 높게 나타났다. 유기산 중 citric acid 함량이 가장 많이 함유되어 있었고 다음으로 succinic acid, malic acid, acetic acid, formic acid 순으로 검출되었다. 총 폴리페놀 및 플라보노이드 함량은 각각 21.66 mg/g, 42.78 mg/g으로 나타났다. Streptococcus mutans에 대해 죽엽 추출물 0.04% 이상에서, Streptococcus sobrinus에 대해서는 0.16% 이상에서, Porphyromonas gingivalis와 Prevotella intermedia에 대해서는 0.02% 이상에서 강한 항균 활성이 인정되었다. S. mutans, S. sobrinus, P. gingivalis, P. intermedia는 죽엽추출물 0.32% 농도에서 각각 60시간까지 억제됨을 관찰할 수 있었다. 따라서 본 연구 결과는 죽엽 에탄올 추출물이 구강질환을 유발하는 세균에 대하여 우수한 항균작용을 나타내고 있으며, 따라서 죽엽이 구강질환 예방에 긍정적인 효과가 있을 것으로 생각한다.